Age of Starting School, Academic Performance, and the Impact of Non-Compliance: An Experiment within an Experiment, Evidence from Australia - Tony Beatton; Michael Kidd; Anthony Niu; Francis Vella (Institute of Labor Economics (IZA), 2021)
This paper estimates the difference in academic performance of the oldest and youngest students in a given grade. We employ Queensland Department of Education school administration panel data for the population of state school students for the years 2008-2016. Academic performance is measured by National standard test scores (NAPLAN) and teacher assessed measures of performance and effort for individuals in grades 3, 5 and 7. The empirical analysis employs a regression discontinuity design (RDD) based on administrative rules on age of school enrolment. The class assigning mechanism operates via a known cut-off date and results in the oldest child in the grade being almost a year older than the youngest. However, as parents may anticipate a disadvantage in their child being the youngest in grade they may choose to delay the timing of initial enrolment. This lack of compliance potentially creates difficulties for the RDD identification strategy, in particular the assumption of exchangeability around the cut-off. We exploit a change in the cut-off rule from a 2008 reform which postponed the school starting age by 6 months and produced a large increase in the compliance rate. This enables one to gauge the importance of non-compliance in estimating the treatment effect of being older versus younger in cohort. We find that the pre-reform treatment effect is small and generally statistically insignificant. Post-reform there is a sizeable and statistically significant treatment effect which diminishes as the sample proceeds through school grades, 3, 5 and 7.
Keywords: I29; 330; national standard achievement tests; compliance rates; fuzzy regression discontinuity